Global neoproterozoic petroleum systems : the emerging potential in North Africa - Craig, J. (Geological Society, 2009)
This volume focuses on recent developments in the understanding and correlation of North African basin fills and explores novel approaches to prospecting for source and reservoir rocks. The papers cover aspects of petroleum prospectivity and age-equivalent global petroleum systems, Neoproterozoic tectonics and palaeogeography, sequence stratigraphy, glacial events and global climatic models, faunal and floral evolution and the deposition of source rocks.
Keywords: Petroleum -- Geology -- Africa, North.; Hydrocarbon reservoirs -- Africa, North.; Paleogeography.; Sequence stratigraphy.; elektronické knihy; electronic books